2005
DOI: 10.1242/jcs.02461
|View full text |Cite
|
Sign up to set email alerts
|

Calcium mobilization stimulatesDictyostelium discoideumshear-flow-induced cell motility

Abstract: Application of hydrodynamic mild shear stress to adherent Dictyostelium discoideum vegetative cells triggers active actin cytoskeleton remodeling resulting in net cell movement along the flow. The average cell speed is strongly stimulated by external calcium (Ca2+, K50%=22 μM), but the directionality of the movement is almost unaffected. This calcium concentration is ten times higher than the one promoting cell adhesion to glass surfaces (K50%=2 μM). Addition of the calcium chelator EGTA or the Ca2+-channel bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 50 publications
8
88
2
Order By: Relevance
“…In fact, purified G proteins in phospholipid vesicles were activated in response to acute shear stress in the absence of other protein components (23). However, cells lacking β or γ subunits of G proteins migrate more slowly randomly, in chemotaxis, electrotaxis, and shear flow, and are deficient in phagocytosis, suggesting that the defect in mechanosensitivity might be related to the decreased baseline activity (13,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, purified G proteins in phospholipid vesicles were activated in response to acute shear stress in the absence of other protein components (23). However, cells lacking β or γ subunits of G proteins migrate more slowly randomly, in chemotaxis, electrotaxis, and shear flow, and are deficient in phagocytosis, suggesting that the defect in mechanosensitivity might be related to the decreased baseline activity (13,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Fache et al previously reported reduced shear-flow-induced motility for cells lacking G β (13). Thus, we examined whether heterotrimeric G proteins are involved in the response to acute stimulation with shear flow.…”
Section: Role Of the Signal Transduction Network In The Response To Amentioning
confidence: 94%
“…All Michaelis constants are also dimensionalized by d: (1) in the normalized form is transformed as follows:…”
Section: Methods the Model Equationsmentioning
confidence: 99%
“…Amongst many other factors, intracellular Ca 2+ has been shown to modulate both the speed and direction of Dictyostelium motility. 1 In an attempt to shed light on the above issues, we employed our model to develop the following testable hypothesis. We sought to investigate whether or not the Ca 2+ surges caused by the application of calmidazolium added at different time points of the oscillatory cycle would result in similar phase delays in optical density oscillations to those observed experimentally in ref.…”
Section: A New Model For Camp Oscillations In Dictyostelium Exhibits mentioning
confidence: 99%
See 1 more Smart Citation